(untitled) (New York, 1980)
This book introduce about industrial development and characteristics. The three major industrial regions. Other industrial regions. Development and distribution of the main manuafacturing industries. Development and distribution of the main manuafacturing industries. Industrial location policy and environmental issues.
Keywords: Công nghiệp,Industries; Nhật Bản,Japan